On the medium access control protocols suitable for wireless sensor networks – a survey - Guerroumi, Mohamed; Pathan, Al-Sakib Khan; Badache, Nadjib; Moussaoui, Samira (Kohat University of Science and Technology, Pakistan, 2014)
MAC (Medium Access Control) protocol has direct impact on the energy efficiency and traffic characteristics of any Wireless Sensor Network (WSN). Due to the inherent differences in WSN’s requirements and application scenarios, different kinds of MAC protocols have so far been designed especially targeted to WSNs, though the primary mode of communications is wireless like any other wireless network. This is the subject topic of this survey work to analyze various aspects of the MAC protocols proposed for WSNs. To avoid collision and ensure reliability, before any data transmission between neighboring nodes in MAC layer, sensor nodes may need sampling channel and synchronizing. Based on these needs, we categorize the major MAC protocols into three classes, analyze each protocol’s relative advantages and disadvantages, and finally present a comparative summary which could give a snapshot of the state-of-the-art to guide other researchers find appropriate areas to work on. In spite of various existing survey works, we have tried to cover all necessary aspects with the latest advancements considering the major works in this area.